Masterclass, Conservatoire Jean Wiéner de Bobigny - Beghin, Tom (Bobigny, France Conservatoire Jean Wiéner de Bobigny, 2023)
Organized by Luca Montebugnoli8 students, playing Mozart, Haydn, Clementi, SchumbertAnton Vasiukovich, Mozart K 570Elise Göckel, Haydn Hob XVI:42Hyunji Kim, Haydn Hob. XVI:50Chika Shibata, Haydn, F Minor Variations, Hob, XVII:6Darren Shen, Clementi F-sharp minor sonata, op. 25 No. 5Wei-Ting Hsieh, Schubert A Major Sonata D 664Keigo Mukawa, Mozart K 280Miyu Ota, Mozart K 282
FRIS
Editorial review
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850